Developments in data extraction, management, and analysis - Do, Nhung; Rahayu, Johanna Wenny 1963-; Torabi, Torab (Premier reference source, 2013)
"This book is an essential collection of research on the area of data mining and analytics, presenting the most recent perspectives on data mining subjects and current issues" - Provided by publisher